Networked Carbon Markets : The Regulatory Framework to Support Carbon Market Linkage--A Concept Paper - Zaman, Peter; Hedley, Adam (World Bank, Washington, DC, 2017)
This paper considers the regulatory frameworkthat is required to be put in place in order to support theestablishment of carbon market linkages, in particular,in light of the bottom-up approach contemplated by theParis Agreement. Section two describes the key purpose ofthe paper and details the assumptions and other factorsthat are made in this paper concerning ‘networking’—aform of linking contemplated by the World Bank Group’s Networked Carbon Markets (NCM) initiative. The key assumption in the paper is that the parties seeking to link two or more carbon markets will, before considering theregulatory elements required for linking, have concluded that there must be political, administrative and/oreconomic rationale for linking. Section three considers the impact of the Paris Agreement, in particular Article 6, on carbon market linkage.Section four introduces the concepts of governance, legal and regulatory frameworks and seeks to draw a distinction between these three concepts, whilst recognising there is a degree of overlap.In section five discuss the regulatory framework that we consider to be necessary for carbon market linking when considered in the context of traditional linkage models (i.e., those that require greater homogeneity in order to establish linkages).In section six analyses a number of existing trading arrangements to assess whether they offer a suitable foundation for future linked carbon markets. This would potentially enable existing regulatory frameworks to be used as a means of jump-starting the linkage process.Section seven includes a more detailed discussion of the World Bank Group’s proposal for networking and the concept of mitigation value (MV) which is a fundamental element of networking. We consider the variety of modalities for linking, including the networking modeland the NCM transaction scenarios discussed in the NCM Concept Paper. This relates to the acceptance by one country of its MV assessment by a third party assessor. Although we highlight some of the new challenges this will throw up, we conclude that further development about how MV could be operationalised will be required before guidance on the regulatory frameworkfor networking can be further advanced.